ANALYSIS OF TEACHERS’ PERCEPTION ON THE USE OF E-LEARNING PLATFORM AT SMP NEGERI 37 MEDAN - Bryan Brahma T. Pasaribu; Isli Iriani Indiah Br. Pane (Universitas Negeri Medan, 2022)
The purpose of this study is to describe how teachers at SMP Negeri 37 Medan feel about using the E-learning platform by using Google Classroom Apps. The study was carried out with the use of descriptive qualitative analysis. It was conducted at SMP Negeri 37 Medan. The information was acquired through a Google form questionnaire and interviews. According to the findings of the study, the first and second teachers believe that Google Classroom teachers cannot fully assist teachers in the teachinglearning process in the virtual classroom. Teachers favor on-line instruction. Teaching online with Google Classroom necessitates additional effort, such as internet access and time extensions. It is also believed that teachers have difficulty disciplining students during the teaching learning process. The findings of the study show that two teachers’ perceptions of teachers on the use E- learning platform by using Google Classroom Apps during the learning process in Covid 19 are positive, and that using Google Classroom has forced teachers to be more creative in their teaching learning process.Keywords: perception, teachers’ perception, e-learning, Google Classroom